2011
DOI: 10.1016/j.vetimm.2010.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the peripheral blood lymphocyte populations in multiparous rabbit does with two reproductive management rhythms

Abstract: The emergence of epizootic rabbit enteropathy is leading to changes in weaning protocols in 25 commercial rabbitries. Traditional weaning protocols are being replaced with late weaning, 26 beyond 35 days postpartum (dpp). The main objectives of this study were to compare the 27 peripheral blood lymphocyte populations of multiparous rabbit does under two reproductive 28 rhythms (insemination at 11 dpp and weaning at 28 dpp, insemination at 25 dpp and weaning 29 at 42 dpp), and to assess the influence on those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
3
19
1
Order By: Relevance
“…As reported in a previous study (Guerrero et al, 2011), where a similar methodology was used, several imbalances appear in the results obtained in the present study: (1) the sum of the CD5+ and B lymphocyte percentages is lower than 100 and (2) the sum of the CD4+ and CD8+ lymphocytes is lower than the number of T CD5+ lymphocytes.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As reported in a previous study (Guerrero et al, 2011), where a similar methodology was used, several imbalances appear in the results obtained in the present study: (1) the sum of the CD5+ and B lymphocyte percentages is lower than 100 and (2) the sum of the CD4+ and CD8+ lymphocytes is lower than the number of T CD5+ lymphocytes.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 84%
“…Although rabbits have been traditionally used as experimental models for many years, data about their blood lymphocyte populations are scarce. This lack of information is more evident in commercial rabbits (Guerrero et al, 2011) where it is vital to characterise and to evaluate rabbit genetic lines and their responses to different challenges, like heat stress, which is the case in this study.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results would reflect the importance of not moving too far from the appropriate body status to ensure reproduction and reduce the risk of culling. Thus, Guerrero et al (2010) and Ferrian et al (2012) observed a positive correlation between the body status of the rabbit does and the population of B lymphocytes (from +0.40 to +0.82) and that there is a positive correlation between the lymphocyte populations of the does and their litters (e.g. T CD5+: +0.35).…”
Section: Robustnessmentioning
confidence: 91%
“…Chronic exposure to such a stressor could have immunosuppressive effects (von Holst, 1998). Indeed, such a relationship between extended lactation and alterations in immune status has been shown in the domestic rabbit (Guerrero et al, 2011). In addition, injury of the teats and related diseases are also common.…”
Section: Housingmentioning
confidence: 99%